Spatial Variability and Hotspots of Methane Concentrations in a Large Temperate River - Bussmann, Ingeborg; Koedel, Uta; Schütze, Claudia; Kamjunke, Norbert; Koschorreck, Matthias (Frontiers in Environmental Science, 2022)
Rivers are significant sources of greenhouse gases (GHGs; e.g., CH4 and CO2); however, our understanding of the large-scale patterns of GHG emissions from rivers remains incomplete, representing a major challenge in upscaling. Local hotspots and moderate heterogeneities may be overlooked by conventional sampling schemes. Here, we performed continuous CH4 measurements during a 584-km-long river cruise along German Elbe to explore heterogeneities in CH4 concentration at different spatial scales and identify CH4 hotspots along the river. The highest CH4 concentrations were recorded at known potential hotspots, such as weirs and harbors. These hotspots were also notable in terms of atmospheric CH4 concentrations, indicating that measurements in the atmosphere above the water are useful for hotspot detection. We observed only moderate changes and fluctuations in values along the river. Tributaries did not obviously affect CH4 concentrations in the main river. The median CH4 emission was 251 µmol m-2 d-1, resulting in a total of 28,640 mol d-1 from the entire German Elbe. Similar numbers were obtained using a conventional sampling approach, indicating that continuous measurements are not essential for a large-scale budget. However, we observed considerable lateral heterogeneity, with significantly higher concentrations near the shore only in reaches with groins. Sedimentation and organic matter mineralization in groin fields evidently increase CH4 concentrations in the river, leading to considerable lateral heterogeneity. In conclusion, groin construction is the second anthropogenic modification following dam building that can significantly increase GHG emissions from rivers.